Handwritten signature recognition for forgery detection / Izzah Atirah Shammudin - Shammudin, Izzah Atirah (2022)
Image enhancement methods are widely used in a variety of picture processing applications where image subjective quality is vital for human interpretation. In any subjective assessment of image quality, contrast is critical. The difference in brightness reflected from two nearby surfaces creates it. Contrast, in particular, is the distinction in visual qualities that makes an item identifiable from other objects as well as the background. Contrast is defined visually by the separation between the colors and brightness of the objects. Several techniques for producing contrast enhancement are being developed and applied to image processing. “Once the image of a handwritten signature for a customer is captured, several pre-processing steps are performed on it including filtration and detection of the signature edges.” (Hussein, Salama, & Ibrahim, 2016)